Current state and tendencies of development production systems - E. A. Bayda (Вестник СибАДИ)
In this article the question of a possibility of creation and introduction at the Russian enterprises of own production systems on the basis of synthesis of foreign and domestic experience of use of instruments of economical production for the purpose of decrease in costs of production, temporary losses and increase of labor productivity as one of the most important indicators of social and economic development of the country is considered. Also expediency and timeliness of introduction of national standards on economical production as instruments of effective production management is proved in article.